PEMERIKSAAN PERKARACERAI TALAK DAN CERAI GUGATDI PERADILAN AGAMA - Asnaini Asnaini; Rochmatun Rochmatun (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2015)
Investigation The Case of Divorced By Talak And Sued Divorce In The Religious Courts.In judicial proceedings in the Religious Courts shall apply the provisions of the law courts in the eventthe General Court inter alia contained in HIR (Herziene Indonesisch Reglement) for Java and Madura,R.Bg (Rechts Reglement voor de buitengewesten) for outside Java and Madura, Book IV of theevidence and the expiration BW (Burgerlijk Wetboek), Rv (Reglement op de Rechtsvodering), LawNo. 20 of 1947 on the Judiciary Deuteronomy in Java and Madura and so on, unless it has beenspecifically regulated in Law No. 7 of 1989 as amended by Act No. 3 of 2006 and Act No. 50 of 2009on the Religious Courts as well as the provisions of the Islamic Law Compilation